2002
DOI: 10.1007/s00436-001-0567-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic study of Theileria sp. (Thung Song) based on the thymidylate synthetase gene

Abstract: Theileria type Thung Song is an indigenous hemoparasite of dairy cattle from the south of Thailand. It has previously been classified using the analysis of a comparative set of small subunit ribosomal RNA nucleotide sequences. However, the classification of this parasite is still questionable since the Theileria type Thung Song was located as the intermediate parasite between pathogenic and benign groups. We use the thymidylate synthetase gene (TS) as an alternative for the rapid molecular phylogenetic tree co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Theileria sergenti has been found to be associated with the infection of cattle in East Asia (Kubota et al, 1996;Choi et al, 1997), Southern Asia (Wang et al, 1998;Chansiri and Sarataphan, 2002) and Europe (Savini et al, 1999). Generally, the diagnosis of the T. sergenti infection is determined by detecting T. sergenti parasites in Giemsa-stained thin blood smear films by light microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Theileria sergenti has been found to be associated with the infection of cattle in East Asia (Kubota et al, 1996;Choi et al, 1997), Southern Asia (Wang et al, 1998;Chansiri and Sarataphan, 2002) and Europe (Savini et al, 1999). Generally, the diagnosis of the T. sergenti infection is determined by detecting T. sergenti parasites in Giemsa-stained thin blood smear films by light microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Theileria sp. Thung Song is an isolate from dairy cattle in Thailand and was genotypically divergent from other benign T. orientalis types ( T. buffeli and T. sergenti ) [ 51 , 52 ]. Its detection in goats in the current study may indicate host shifting of this parasite.…”
Section: Discussionmentioning
confidence: 99%
“…His group used the thymidylate synthetase gene (TS) for the phylogentic analysis of Theileria sp. (type Thung Song), T. buffeli and Theileria sergenti and found that the latter two parasites are closely related and that Theileria type Thung Song is distantly related to them (Chansiri and Nopporn 2002). Pylogentic analysis of all Theileria 18S ribosomal RNA genes allowed for a subdivsion into eight clusters.…”
Section: Diagnosis Identification and Discriminationmentioning
confidence: 98%